Examining English as a Foreign Language Students' Boredom in terms of Different Variables - Coşkun, Abdullah; Yüksel, Yücel (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
The aim of this study is to adapt the Boredom in Practical English Language Classes-Revised (BPELC-R) scale developed by Pawlak, Kruk, Zawodniak and Pasikowski (2020) into the high school English as a Foreign Language (EFL) context of Turkey and to reveal high school EFL students' level of boredom. Also, the study investigates whether their level of boredom differs depending on the variables of gender, grade level and selected academic track. The two-factor scale including 23 Likert-scale items were completed by 680 high school EFL students at different grade levels in eight public high schools in a city in Turkey. The data analyzed by means of the SPSS uncovered medium level of boredom. It was also found that the most common causes of boredom are the monotonous nature of the English lessons and the dissatisfaction of the participants with these lessons. While no significant difference was observed in the level of boredom depending on the gender variable, students' grade level and the chosen academic track led to significant differences. The highest level of boredom was revealed for final year students and for those who chose the science track. Some implications on how to reduce EFL classroom boredom are provided.